Fine structure of the brain in Amphinomida (Annelida). (3rd May 2021) - Beckers, Patrick; Tilic, Ekin
Abstract: Amphinomida, some also known as fireworms, are not only notorious for their painful sting but also their painfully difficult phylogenetic placement. Current understanding of the annelid tree of life suggests a close affinity with Sipuncula, the unsegmented and sessile peanut worms. This sister‐group relationship is hard to explain from a morphological perspective. Here, we present the results of our histological and ultrastructural study of the central nervous system in two distantly related amphinomids: Euphrosine foliosa (Euphrosinidae) and Eurythoe complanta (Amphinomidae). We provide detailed morphological information, aiming to set up the groundwork for future comparative studies and to gain insight into the evolution of annelid nervous systems. We not only compare our observations among the two species but also discuss their implications for annelids in general and more specifically for the sipunculan affinity. The central nervous system in Amphinomida differs both from other errantian annelids and also from Sipuncula and shows no clear synapomorphies that would argue for or against their current phylogenetic placement.